Annual Plan 2003-2004 West Bengal - Planning Commission (Planning Commission, 2003)
In my foreword to the Annual Plan, 2002-2003,I had noted that against the background of worldwide recessionary trend and all pervasive effect of globalisation the task of preparation of Annual Plan of the State Government functioning within the framework of the constitution is a critical job and it is more so because of the increasing role of the market force in determining the course of our economy. At the end of the first year of the 10th Plan there has been no substantial change in the situation. Rather, the fiscal problem of the last years has further aggravated and now assumed serious proportions. It is needless to mention that the financial problems of the states basically stem from the high debt and interest burden and rising salary and wage bills. We have been impressing the Government of India for the last several years on the urgency of providing adequate relief to the States for mitigating this acute problem and help thrive the States' economy but no tangible results have followed so far. In the last meeting of the National Development Council held on December 21, 2002 in New Delhi we argued strongly for application of prevalent low rate of interest in respect of outstanding debts of the States and taking new initiatives for providing effective debt relief to them.
Development and Planning Department, Government of West Bengal
Development and Planning Department Government of West Bengal